Anticipated Role of Bangladesh Police in Disaster Management Based on the contribution of Bangladesh Police during the Pandemic Covid 19 - Fatema Islam (Critical Disaster Studies, 2023)
This article explores the contribution of Bangladesh Police as a first responder in the pandemic Covid 19 in the recent years. Bangladesh police played a vital role in maintaining law and order situation during prolonged lockdown, building awareness among mass people, ensuring safe transportation and mobility, and assisting people in humanitarian ground. The article also identifies the anticipated potential responsibility of Bangladesh police in pre-disaster planning and post-disaster response based on the experience gathered during the pandemic. Bangladesh police faces some challenges regarding participating in disaster management task actively, such as limited resources, want of communication channel among various govt and non-govt agencies, and limited preparedness. The article founds that during any kind of disaster, Bangladesh Police can enhance their service towards the citizens through effective planning, training, utilizing modern technology, and willingness.
Keywords: Bangladesh Police; Disaster management; Covid 19; pandemic; pre-disaster; post-disaster.